2017
DOI: 10.1063/1.4990392
|View full text |Cite
|
Sign up to set email alerts
|

Spreading resistance at the nano-scale studied by scanning tunneling and field emission spectroscopy

Abstract: We explore the capability of scanning tunneling microscopy (STM) and scanning tunneling spectroscopy (STS) to study nanoscale Si(100) device layers in silicon-on-insulators (SOIs). These device layers are a macroscopic 2D silicon sheet, and understanding the effective coupling of charge in and out of this sheet allows the determination of whether it is possible to accurately measure the electronic properties of the sheet. Specifically, we examine how the spreading resistance is manifested following the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Besides FER peaks, transmission resonance signals can be observed when the sample is Ag films. 9,10) FER has been used to observe the dynamics 11,12) and lateral quantization of hot electrons on the surfaces, [13][14][15] the atomic structure of an insulator, 16) plasmon-assisted electron tunneling, 17) nanoscale resistance, 18) surface reconstructions, 19,20) and energy gap. 21) Moreover, studies have demonstrated that FER energies can be used to determine the difference in the work functions of films and substrates [22][23][24][25][26][27][28][29][30][31] and the electric field for forming quantized states that cause FER peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Besides FER peaks, transmission resonance signals can be observed when the sample is Ag films. 9,10) FER has been used to observe the dynamics 11,12) and lateral quantization of hot electrons on the surfaces, [13][14][15] the atomic structure of an insulator, 16) plasmon-assisted electron tunneling, 17) nanoscale resistance, 18) surface reconstructions, 19,20) and energy gap. 21) Moreover, studies have demonstrated that FER energies can be used to determine the difference in the work functions of films and substrates [22][23][24][25][26][27][28][29][30][31] and the electric field for forming quantized states that cause FER peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Since Binning et al and Becker et al observed FER using STM [2,3], FER has been a powerful technique widely exploited to investigate the surface reconstructions [4,5] and properties [6], the atomic structure of the insulator surface [7], local work functions [8][9][10][11][12], the resistance at the nanometer scale [13], as well as the dynamics [14,15] and lateral quantization [16,17] of surface electrons above the vacuum level. Our recent studies have demonstrated that the field enhancement factor and sharpness of an STM tip can be qualitatively identified by counting the number of FERs [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In an STM junction, the form of the external potential (FEP) that generates FERs was assumed in previous studies to be triangular [9,10,12,13,18]. This assumption implies that the structures of the tip and sample are parallel plates.…”
Section: Introductionmentioning
confidence: 99%